Electrical spectroscopy of earth materials - Levitskaya, Tsylya M.; Sternberg, Ben K. (Elsevier, 2019)
Electrical Spectroscopy of Earth Materials provides detailed coverage of theoretical and experimental methods of electrical spectroscopy of Earth materials, based on first-hand research and extensive data. The book includes actual data sets and specific explanations for the methods used in obtaining and analyzing the data, including graphical displays of results. It describes the electrical properties of various soil samples and offers both theory and techniques for researchers to apply to their own research. Including examination of the practical aspects of electrical spectroscopy measurements and extensive computer-readable data, Electrical Spectroscopy of Earth Materials is a unique resource for geophysicists to save both time and effort in understanding and analyzing Earth materials and soil properties.